Defying distance: exercise providers’ perspectives on remote physical activity supports for older adults: a mixed-methods study - Mehrabi, Samira; Drisdelle, Sara; Dutt, Hanna R.; Middleton, Laura E. (Frontiers in Public Health, 2025)
IntroductionMany older adults encounter barriers to participating in physical activity programs, often due to cost, accessibility, and transportation challenges. Implementing feasible and effective remote support strategies may enhance their physical activity participation. This mixed-methods study examines exercise providers’ use of remote supports for physical activity among older adults, their perceived effectiveness, and barriers and facilitators to adoption during the COVID-19 pandemic and beyond.MethodsExercise providers (≥18 years) completed a web-based survey (June–September 2020), and optional semi-structured interviews (September–December 2020), guided by the COM-B model. Participant characteristics, uptake and perceived effectiveness of remote supports, and presence and severity of barriers were explored and analyzed with inductive thematic analysis.ResultsFifty-one exercise providers (age 36.3 ± 12.3 years, 38 female) completed the survey; 86% provided remote support for physical activity, including provision of copy materials (63%) and delivery of real-time virtual programs (59%), with the latter rated the most effective (88%). Key barriers included older adults’ limited technical skills (78%) and access to technology (82%). Interviews (n = 12, age 40.5 ± 15 years, 11 female), yielded five themes: (1) Capacity, Collaboration, and Adaptability Supported Successful Transition to Remote Supports; (2) Tailoring Remote Supports to Needs and Abilities Promoted Safety; (3) Real-time Virtual Programs Fostered Social Support and Engagement; (4) Accessible Technology and Ongoing Support Facilitated Virtual Delivery; and (5) A Hybrid Approach Balances Convenience and Social Benefits.ConclusionDuring the transition to virtual exercise programming during the COVID-19 pandemic, exercise providers widely used remote supports, favoring real-time virtual programs for socialization and supervision. While there were challenges including safety concerns, technological barriers, and engagement, these challenges were met with innovative solutions. A hybrid approach may be the most sustainable model, balancing the accessibility of virtual programs with the social and motivational benefits of in-person exercise.